PERENCANAAN STRATEGIK SISTEM INFORMASI DAN TEKNOLOGI INFORMASI PADA SMA TALINO - Sri Murni (Universitas Bina Sarana Informatika, 2013)
The increasing number of educational institutions led to increasing competition among institutions. In the field of education, information system is the most important thing in winning the competition, given that information is a strategic asset. In modern times such as the current IT planning is necessary in order to provide harmonized support (support and alignment) to strategic planning. The role of IT in supporting the achievement of the strategic planning strategies may be necessary to find a solution to the GAP between the IS / IT which has been owned by the supposedly exist. The application of information technology systems would be beneficial if the application in accordance with the objectives, vision and mission of the company to establish the strategy of information technology systems are aligned with business strategy.Talino High School is a private high school that is moving under the Housing Foundation (General Education) in which this school is not implementing the IS / IT. For the planning of the IS / IT needed to support the primary activities and support activities at the school.Form of strategic planning of IS / IT to be discussed in the research that will be done is to use the methodology and Peppard ward , with the input of the internal environment of business analysis , business analysis of the external environment , environmental analysis / IT internal environmental analysis / IT external. The results of the study are expected to produce ususlan regarding strategic planning of IS / IT at SMA Talino.Key words: Strategic Planning, IS / IT, SMA Talino